THE SHANGHAI COOPERATION ORGANIZATION (2001-2011): TASKS, RESULTS, AND PROSPECTS - ARUNOVA, Marianna (CENTRAL ASIA AND THE CAUCASUS, 2011)
On 15 June, 2011, the tenth anniversary summit of the Shanghai Cooperation Organization (SCO) was held in Astana. The declaration adopted at the summit stated in particular that “the decision to create the SCO was a strategically calculated step,” while “the choice made by the SCO member states at the beginning of the 21st century to intensify good neighborly, friendly, and partner relations in the region was a commendable example for the world community. Its member states … have laid a strong foundation for the organization’s efficient functioning aimed at jointly ensuring peace, security, and stability, as well as developing multifaceted cooperation in the SCO expanse in the political, economic, humanitarian, and other spheres.” The SCO has indeed become a phenomenon of global dimensions. During the first years of the organization’s existence, the necessary regulatory framework and relevant institutions for carrying out its activity were set up. Several dozen essential documents were signed, such as the SCO Charter, the Treaty on Long-Term Good-Neighborly Relations, Friendship, and Cooperation, the Shanghai Convention on the Fight Against Terrorism, Separatism, and Extremism, the Agreement on Cooperation in the Fight Against the Illicit Circulation of Drugs, Psychotropic Substances, and Their Precursors, the Agreement on Cooperation in the Fight against Crime, the Agreement on Cooperation in Ensuring International Information Security, and other intergovernmental agreements. Over the past years, the system of SCO structures (which includes the Council of Heads of State, the Council of Heads of Government, the Council of Foreign Ministers, and the Council of National Coordinators) has been supplemented with annual meetings of the secretaries of the member states’ security councils and regular sittings of the defense and internal affairs ministers and the heads of anti-drug departments. The SCO Secretariat has been established in Beijing, while the SCO regional antiterrorist structure (RATS) functions in Tashkent. Mechanisms of interbranch cooperation (from the expert to the ministerial level) have been set up and a whole series of specific cooperation projects in various areas have been launched. The international community’s recognition of the SCO is proof of its growing significance; for example, the U.N. granted the organization the status of observer and signed a memorandum on cooperation with it. Such structures as ESCAPO and the U.N. Office on Drugs and Crime, as well as many regional organizations, including the CSTO, EurAsEC, CIS, and ASEAN, have established official contacts with the SCO. As of today, India, Iran, Mongolia, and Pakistan are observers in the SCO, and Belarus and Sri Lanka are dialog partners; representatives of Afghanistan and Turkmenistan participate in some of the organization’s undertakings. The SCO’s potential is not merely the arithmetic sum of the potential of its participating states, although the fact that China and Russia are members gives it enough of a name in itself. The SCO is an entity of qualitatively new dimensions; most experts think that its appearance in the region has given rise to a force capable of realistically opposing the challenges and threats to security and has become an important component of the geopolitical landscape (regional and even global). At the same time, it is obvious that the evolution of the world situation, the events in Afghanistan and Central Asia (CA), and the economic integration and energy cooperation processes in the Eurasian expanse are making ever higher demands on the regional organizations functioning here. In this respect, very legitimate questions arise: “Does the SCO meet these demands? What is the real potential of this organization currently celebrating its anniversary? What vectors and forms could the organization’s transformation take in the short and mid-term, keeping in mind the forecasted development of events, and how will this affect the interests of its members, statutory goals, and practical capabilities?”